Knowledge and skills required to perform point-of-care ultrasonography in family practice – a modified Delphi study among family physicians in Slovenia - Homar, Vesna (BMC Fam Pract, 2020)
BACKGROUND: More and more family physicians (FPs) are using point-of-care ultrasonography (POCUS) in Europe. Still, there is no general consensus about the specific knowledge and skills that a FP should acquire in order to effectively perform POCUS. The objective of this study was to identify indications for the use of POCUS among FPs, explore the barriers of its use and provide an expert opinion of FPs on knowledge and skills required to effectively implement POCUS in family practice. METHODS: A modified two-round Delphi study was carried out among FPs using POCUS in Slovenia. RESULTS: 21 FPs were invited to participate in the study. A total of 13 FPs (62%) responded the round-one questionnaire and 10 (48%) completed the round-two questionnaire. Results show a large variability of indications for the use of POCUS in family practice, the most common being acute abdominal conditions, lung ultrasonography and eyeballing echocardiography. In contrast, the results show little variability in barriers for the use of POCUS, the most common being lack of time, inaccessibility of specific training programmes and financial issues. There is a strong consensus on the knowledge and skills needed to perform POCUS. Panellists agreed on a learning medical knowledge, technical skills and expressed a need for individual consultations and tutorship options. CONCLUSION: This study proves that although POCUS is used in family practice for a wide variety of indications with a significant number of barriers, there is a strong consensus on what a FP needs to know to effectively perform POCUS.